Power, Privilege And Sex Education in Irish Schools, 1922-67: An Overview - O’Donoghue, Tom; Harford, Judith (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
An overview of the thinking that led us to write our most recent book, Piety and Privilege. Catholic Secondary Schooling in Ireland and the Theocratic State, 1922-67, constitutes the substance of this paper. Our central argument is that during the period 1922-1967, the Church, unhindered by the State, promoted within secondary schools, practices aimed at “the salvation of souls” and at the reproduction of a loyal middle class and clerics. The State supported that arrangement with the Church also acting on its behalf in aiming to produce a literate and numerate citizenry, in pursuing nation building, and in ensuring the preparation of an adequate number of secondary school graduates to address the needs of the public service and the professions. This situation proved attractive to successive governments, partly because the great majority of the nation’s politicians and public servants were themselves loyal middle-class Catholics. In addition, the teaching religious played a crucial role in the State’s project of harnessing schools as part of its Gaelic nation-building project. This paper considers what we deem to be three distinctive aspects of our work. First, we detail how it is a contribution not just to the history of education in Ireland but also to the broader field of the history of Catholic Church and State relations in education in the English-speaking world for the period examined. Secondly, we deliberate on the research approach we adopted in generating our exposition. Thirdly, we outline our consideration of three aspects of the process of education in Catholic schools that have been neglected in many accounts to date, namely, the manner in which privilege, piety, and sex education were approached.